Note on the natural density of r-free numbers - Sunanta Srisopha; Teerapat Srichan; Sukrawan Mavecha (My University, 2022)
Let P be a finite set of prime numbers. By using an elementary method, the proportion of all r-free numbers which are divisible by at least one element in P is studied.
Keywords: Natural number; Natural density; Analytic Number Theory Research